IMPLEMENTATION OF THE SCRUM MODEL IN THE DEVELOPMENT OF ONLINE SALES SYSTEMS OF MSMEs DURING THE COVID-19 PANDEMIC - Wahyutama Fitri Hidayat; Annida Purnamawati; Fajar Sarasati (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2021)
A global pandemic or epidemic indicates a covid-19 infection that is very fast spreading throughout the world, including Indonesia. This has an impact on several sectors, one of which is the economic sector. There are various things that have caused the economic sector to be touched by the impact of the covid-19 virus, including government policies at both the central and regional levels that issued several regulations relating to restrictions on community mobility. Indirectly, things related to mobility restrictions or what is currently known as Pembatasan Sosial Berskala Besar (PSBB) have an impact on consumer behavior to switch to making purchases online. To address this, the online sales system is considered to be a solution for MSMEs to continue the buying and selling process. Using the Scrum model as a more efficient system development, feedback between users and developers who can work better to create a more interactive system. The results of this study are a website that can be used by UMKM as a means of selling their business products amid the Covid-19 pandemic.